2003
DOI: 10.1063/1.1555263
|View full text |Cite
|
Sign up to set email alerts
|

Large conductance switching and memory effects in organic molecules for data-storage applications

Abstract: We have observed a large electrical conductance switching (ON:OFF ratio=105) in single-layer sandwich structures based on organic molecules at room temperature. The switching devices showed an associated memory effect for data-storage applications. We could write or erase a state and read it for many cycles. In switching devices, the active semiconductor retained its high conducting state until a reverse voltage erased it. A high conducting state arose due to restoration of conjugation in the molecule via elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(81 citation statements)
references
References 13 publications
(8 reference statements)
2
78
1
Order By: Relevance
“…Furthermore, the magnitude of the currents shown here is higher than observed by Bandyopadhyay and Pal. 13 They also observed switching in rose bengal devices contacted by different top electrodes, e.g., mercury top electrodes, 16 which hints that the effect they observed has a different origin. However, the switching effect observed in our devices is a more general mechanism which may be in operation in other molecular devices also.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the magnitude of the currents shown here is higher than observed by Bandyopadhyay and Pal. 13 They also observed switching in rose bengal devices contacted by different top electrodes, e.g., mercury top electrodes, 16 which hints that the effect they observed has a different origin. However, the switching effect observed in our devices is a more general mechanism which may be in operation in other molecular devices also.…”
Section: Discussionmentioning
confidence: 99%
“…This switching behavior is similar to the switching behavior of rose bengal devices described by Jakobsson et al 17 but shows significantly larger currents than the switching shown by Bandyopadhyay and Pal. 13 For later applications, the switching speed of the devices is of fundamental interest. The frequency dependence of the switching voltages is shown in Table II.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported switching times vary by orders of magnitude with values ranging from nanoseconds to milliseconds. [23][24][25][26][27][28][29] As seen in Fig. 6, once programmed into the on-state, even low voltages trigger switching in low current capacity filaments, but still show a delay before the maximum current is achieved.…”
Section: B Transient Response In the On-statementioning
confidence: 99%
“…Recently, considerable attention has been directed toward electrical switching and memory devices which consist of organic materials, polymers and charge transfer complexes with an electrical bistable function [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Memory devices based on organic (polymer) materials have many advantages compared to inorganic memory devices, such as flexibility, simple processing, a low cost, and largearea fabrication via printing technology.…”
Section: Introductionmentioning
confidence: 99%